Changes in the bioclimate of the Kłodzko region with special regard to health resorts - Głogowski Arkadiusz (Uniwersytet Przyrodniczy we Wrocławiu, 2022)
The dissertation main objective is to conduct comparative analysis of biometeorological conditions in health resorts located in the Kłodzko Region on the basis of long-term meteorological measurements and own research.
W wersji elektronicznej dostępne wyłącznie streszczenie rozprawy doktorskiej
Keywords: UTCI; bioclimatology; time series analysis; nonlinear data reconstruction; macrocirculation phenomena; AMO; NAO